The War of the Pen and the Soekarnoism Support Body in the Visualization of Caricatures by Merdeka - Anggoro Prasetyo; Agus Setiawan (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This article will explain the caricatures made by Merdeka as a response to the pen war that occurred between Merdeka as the main actor along with various other newspapers that sided with BPS (Soekarnoism Supporting Agency). In this case, the author will use historical research methods that rely on various sources, such as newspapers, magazines, books, journal articles, and published sources. The chaos in the years that was the target of the research made journalists aware to immediately look for other alternatives until they agreed to establish the Soekarnoism Support Agency. Apart from that, the characters that are the objects in Merdeka's caricatures seem odd, especially in terms of anatomy. However, Merdeka should still pay attention to the corridors of polite delivery and avoid things that could actually reduce or even eliminate the weight of the caricature.